O medicamento para doença rara como objeto de prestação estatal - Gloeckner, Joseane Ledebrum (2013)
This dissertation had the objective of studying rare disease drugs. For this, we focus on the fundamental, social and positive health right issue as a subjective right and its immediate applicability. It was analyzed the right to a rare disease medication as a part of the right to health and the obligation of the State in provide it, independently of being or not in the drugs list of the Brazilian Public Health System (SUS). In order to provide it by Government, the financing occurs through tax collection and, for this reason, we demonstrate the various forms of health financing, as well as the impossibility of this effectuation in the reserve of the possible limitation. Thenceforth we move to the specific issue of medication, their economic repercussion and the advantages and disadvantages of drugs industrial property recognition by Brazilian Law. Then, we presented the compulsory licensing, the parallel importation and the national manufacture of generic drugs as a way to solve the problem of interruption of production of rare disease drugs by pharmaceutical laboratories. Besides, we made a brief study of public policies for drugs production encouragement to these diseases imposed by USA and European Union. At last, it was demonstrated the need of adoption, also in Brazil, of a specific public policy to encourage the rare disease drugs production as well as the indispensability of the Government create and finance more public pharmaceutical laboratories.